'From where I'm looking it just seems like two people have missed the boat …': understanding set behaviour from a socioanalytic perspective. Issue 5 (20th October 2018) - Shepherd, Gary
Abstract: Accounts of practice within the action learning literature tend to omit the more mundane session-to-session details of the inner-workings of the action learning set. As well as concentrating on the problem, individuals in all sets spend some of their time in unproductive interpersonal exchanges. These exchanges may be considered trivialities and not worthy of mentioning within an account of practice. The behaviour could, however, hold the key to understanding how the action learning group manages its unconscious anxieties associated with problem solving. In this article, using empirical research from his Ph.D. dissertation, the author explores how the insights developed by Wilfred Bion on groups, their unconscious behaviour and the anxiety of problem solving can help both action researchers and set participants better understand the working of their sets.